Biocompatible metal-assisted C–C cross-coupling combined with biocatalytic chiral reductions in a concurrent tandem cascade. Issue 92 (1st November 2018) - Schaaf, Patricia; Bayer, Thomas; Koley, Moumita; Schnürch, Michael; Bornscheuer, Uwe T.; Rudroff, Florian; Mihovilovic, Marko D.
Abstract : We present a concurrent chemo/biocatalytic one pot reaction cascade by combining a metal (Pd/Cu) assisted Liebeskind–Srogl coupling with an enantioselective enzymatic reduction for the production of chiral amines and alcohols. Abstract : In this study, we present a concurrent chemo/biocatalytic one pot reaction cascade by combining a metal (Pd/Cu) assisted Liebeskind–Srogl (L–S) coupling with an enantioselective enzymatic reduction for the production of chiral amines and alcohols. The latter transformation was realized by applying enantiocomplementary alcohol dehydrogenases from Lactobacillus kefir ( R -selective) and Rhodococcus ruber ( S -selective). Compatibility issues were solved by investigating first the L–S-coupling protocol in water at room temperature. Subsequently, we investigated two different biphasic systems and applied a biomimicking approach to separate enzyme-deactivating components. By using a lipophilic membrane in a smart reactor design, we were able to perform concurrent catalytic cascades with overall concentrations up to 100 mM substrate and to produce 1-phenylethylamine and several chiral alcohols in high yields (up to 81% over 2 steps) and enantiomeric purity ((+) and (−)-enantiomers both with 99% ee).